Economic Essence of Value Added Tax - Хома, С. В.; Орлова, В. К.; Кафка, С. М.; Василенко, Н. К. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The value added tax object was considered in accordance with the current legislation. The components of added value and the procedure of their allocation were analyzed. Approaches to reform the VAT by applying alternative methods for determining tax liabilities, that can increase the efficiency of its collection and can consider such main disadvantage of VAT as its reimburse nature, were suggested.